Exploration of Social Media Usage Among Nurses in the European Region - Tiina Syyrilä; Laura Hako; Helena de Rezende; Ippolito Notarnicola; Marie-Louise Luiking; Jill Murphy; Helena Felizardo; Liz Westcott; Ilya Kagan (CIN: Computers, Informatics, Nursing, 2026)
The study aimed to explore nurses’ use of social media for networking, cooperation, and learning purposes. This cross-sectional study collected data from 158 nurses using an online questionnaire, primarily distributed through open social media for Sigma nurses across 19 European countries in 2023. Over half of the respondents were Sigma nursing members [n=105 (66.4%)]. PhD or a second academic degree was held by 58.2% (n=92) of the respondents. The questionnaire examined (1) background characteristics; (2) social media platforms’ use; (3) usage of social media for learning; and (4) networking. WhatsApp, Facebook, and Instagram were the most frequently used social media platforms. While most nurses did not perceive social media as a tool for learning, a significant portion reported using it for receiving, discussing, and posting knowledge, indicating a contradiction in perceptions of learning through social media. Social media was primarily used to stay updated on research, news, and webinars. Barriers to utilizing social media for learning addressed a lack of time, concerns over privacy, user skills, information overload, content reliability, and platform complexity. Social media can enhance learning and networking opportunities for nurses, but platforms must be selected and content tailored to meet their educational needs. Further research is necessary for generalizability, given the limited sample size and representativeness, and to optimize social media strategies for knowledge dissemination. This study adds to the literature by presenting indicative descriptive perspectives of predominantly highly educated nurses in the European region on social media use for professional networking, collaboration, and learning.